Makna Kalalah dan Penindasan Hak Perempuan - Muhammad Rikza Muqtada (Esensia: Jurnal Ilmu-Ilmu Ushuluddin, 2015)
The article discusses the shifting process of free inheritance system (wasiat) into the codified one (ilm al-faraidh). In this shift of system, Hadis serves as its key factor. In the realm of interpretation discourse and Islamic Law, al-Syafi’i pays keen attention on the use of Hadis. In addition, the use of Hadis implicates a sequence of methodologies in order to support certain arguments, such as found in the ijma’.The use of hadis relatively functions as mediation of various ideas, applying particular way toward certain intended conclusion. Having utilized the methodological formulation, Al-Syafi’i, in this regard, situates the involvement in the interpretation of inheritance verses (QS. 4:11-12 and 176). Al-Syafi’i’s view has deeply embedded in al-Thabari, one of the interpreters on the school. Both al-Syafi’i and al-Thabari have implemented Hadis as the main source in interpretating of the inheritance verses. As the result, it reveals the following concluding remarks: 1). the deletion of the wasiat verses with the inheritance ones, 2). the codification of reading in a passive form (yuratsu and yusa), and 3). the codification of “kalalah” meaning becoming all the heirs except mother, father and the children. Although the codification can mediate the debates, it still reveals a further complicated problem.The problem is on the fact that there are some heiress that actually deserved on the inheritance, but they are in the danger of disinheritance. In inheritance context, it serves not only the passing process of the property between previous and recent generations, but it also relates women’s existence and the positionality vis a vis that of men. In a historical investigation and cross-reference, it is profound that the meaning of “kalalah” denoted female in law (wife, daughter in law or probably sister in law) that deserved as the heiress of the man.